Voorveronderstellings in die hantering van die verhouding tussen Ou en Nuwe Testament. 'n Beskrywing na aanleiding van Friedrich Baumgärtel - S. J. P. K. Riekert (Acta Theologica)
The merit of Baumgärtel’s treatment of expressing the relationship between the Testaments in four statements lies in his emphasising the importance of theological presuppositions. Because these presuppositions are not to be argued as expressions of faith, and because every scientific work is based on such presuppositions, this article discusses the following six presuppositions as statements for describing the relationship between the Old and the New Testament. 1. The Bible as canon has authority for the Christian believer. 2. The Bible or Canon comprises two Testaments. 3. Both the Old and the New Testament convey the powerful word of God. 4. Once the believer is touched by the gospel, he experiences the Old Testament as a witness about Christ. 5. This presupposition paves the way for a theological understanding. 6. The Old Testament should be respected as the revelation before Christ.